The role of strategic leadership in knowledge management processes "Diagnostic Study in the Office of the Ministry of Oil - Project Department" - الطائي, علي حسون; محمد, نسرين جاسم; حسين, ضياء محمد (Journal of Economics and Administrative Sciences, 2011)
The research deals with the important and modern two subjects, strategic leadership which have six demotions and knowledge management (four demotions') . the gools & the research is to know the relation & the effect them in the oil ministry (project department) , the sample was (50) persons who works in the department the questionnaire was the tool of data gathering .The research divided to four parties, the first  to the theotical review of the research variables, the second to the research methrology, the third to analysis and discoed the empirical results the last to the conclusions and recommendations .